Família e poder na Paraíba: os Maia de Catolé do Rocha/PB: um estudo de caso sobre práticas endogâmicas - Teruya, Marisa Tayra (1995)
This research studies the correlation between family members and power, through the analysis of endogamy in a family which belongs to the dominant class in the State of Paraíba - the Maia family from Catolé do Rocha. The nethodology adopted in the research was the genealogical analysis related to the analysis of the family's possessions and ocupation of political positions by the members of the Catoleense group. Considering the limitation of documental data, the study reveals a high incidence of practice of endogamy in the Maia family as a strategy for keeping its power.